The Concept of Desertification, Its Causes and Effects, and Treatments - Ali Khazaal Jawad Al-Kulabi (Journal La Lifesci, 2022)
Since the United Nations General Assembly passed two resolutions in December 1974, the term "desertification" has become a part of international development discourse: The first is a call to all countries to pay attention to desertification research and work together to explore its causes and find strategies to prevent it. The decision to organize an international conference on desertification in 1977 was the second. From August 29 to September 9, 1977, the conference was held in Nairobi, Kenya. The term "desertification" seems to have taken the place of prior words like "desert encroachment." Perhaps what we witness when desert sand dunes creep over oasis communities and farms and fill them, as well as when sand dunes crawl over paved highways and trains, contributes to this picture. This is a genuine depiction, however it only depicts a small portion of the problem (less than 10%). The word "desertification" refers to the process by which productive land outside of the desert's natural limits deteriorates and loses its capacity to produce (agricultural crops, pastures, timber and fuelwood) and transforms into a desert that resembles a limited resource. Desertification, in other words, impacts productive lands in dry and semi-arid locations, agricultural fields (rain-fed or irrigated), and grazing lands. The degradation begins as little patches that get larger and more like expanding patches until they converge and combine, becoming an arid band that joins the deserts of the surrounding places as it becomes more like them.